Edukasi manajemen kesehatan mental selama pandemi covid-19 - AZMIARDI, AKHMAD; Sartika, Iik; Rahardjo, Budi; Aulia, Hanifah Dina (Ruang Cendekia : Jurnal Pengabdian Kepada Masyarakat, 2022)
Covid-19 is a disease caused by the SARS-CoV-2 virus and is currently a worldwide pandemic. Pandemic conditions like this have an impact not only on physical health, but can also affect mental health. People feel fear and concern about personal safety. Pandemic conditions like this also have adverse consequences such as layoffs and unemployment which can lead to mental health problems such as stress. Objective: This community service aimed to increase knowledge and skills in maintaining mental health, especially during the Covid-19 pandemic.This community service activity is carried out in 3 stages, namely socialization and mental health education to members of the Village Health Forum (FKD), program formation and the third is program implementation for ±3 months. There was an increase in participants' knowledge after socialization and education and it was statistically significant (p<0.001). The formation of the "Gotong Royong" program which was carried out by FKD members to the community. This activity increases public knowledge about mental health during the Covid-19 pandemic and is expected to prevent the adverse effects of the Covid-19 pandemic. Suggestions for Puskesmas and FKD can carry out these activities regularly.